(Isten)nők és Boccaccio - Molnár, Annamária (Antikvitás & Reneszánsz, 2018)
Giovanni Boccaccio, writing his prosaic works in Latin and researching antique and medieval literary sources, as a philologist faces the question of systematizing and evaluating of Greek-Roman goddesses: were they really goddesses or not? How can he reveal his point of view to his readers? What kind of concept stands out in Genealogia deorum gentilium, and how consciously and consistently he uses that later in De mulieribus claris? What are the similarities and the differences between the portraits of goddesses in these two works? This is a maze of Cereses and Minervas, and the reader himself has to find the way out of it.